Flashbulb memories in the context of group hierarchies: effects of gender, system justification, and social dominance orientation on negative private and public flashbulb memories - Çavuşoğlu, Merve; Kuşdil, Muharrem Ersin (Frontiers in Psychology, 2024)
Research on flashbulb memories (FBMs) has primarily focused on cognitive aspects. However, recent studies indicate that FBMs are closely associated with social and cultural dynamics. This descriptive study explored the structural aspects and psychosocial functions of negative FBMs within the context of intergroup theories, mainly focusing on negative public (coup attempt in Türkiye on July 15, 2016) and private (bad news of a loved one) FBMs. Participants in the main study (N = 233) were selected and grouped based on their social dominance orientations (SDO; high and low groups) and system justification tendencies (SJT; high and low groups), using data from a preliminary survey (N = 1113). In the main study, participants' responses to items on canonical categories, phenomenological aspects, and psychosocial functions of FBMs and their involvement in different protest actions against the coup attempt were compared considering SDO, SJT, and gender. The results show that private FBMs were generally rated higher by participants than public FBMs in all aspects. Although the canonical quality of private FBM did not differ between gender groups, public FBM quality was better in men. Participants in the high-SJT group had higher-quality public FBMs and rated these memories as more functional than participants in the low-SJT group, along with their high levels of protest participation. No differences were observed between the SDO groups for either type of FBM. The findings are discussed in terms of their relevance to group hierarchies and system justification motives. As the first attempt to place the FBM phenomenon in the context of SDO and SJT at the individual level, this study is intended to encourage others to adopt intergroup theories for integrating bottom-up and top-down processes.